2021
DOI: 10.1590/1980-220x-reeusp-2020-0586
|View full text |Cite
|
Sign up to set email alerts
|

Investigation in forensic nursing: trajectories and possibilities of action

Abstract: To theorize and reflect on the possibilities of the forensic nurse’s performance, emphasizing the work as a civil and criminal expert, based on the Brazilian legislation, ethical principles, and comprehensive care for human beings. This is a theoretical study of exploratory nature with reflective and critical characteristics. It was based on the history of the national and international development of the forensic nursing specialty. It is organized into four categories, namely: areas of practice of forensic nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 10 publications
0
13
0
4
Order By: Relevance
“…As for the year, it was identified that the first publication was carried out in 1995 ( 17 ) , two new publications in 2001 ( 20 ) , one more in 2003 ( 21 ) and another in 2004 ( 22 ) , three publications in 2005 ( 38 ) one more was found, four in 2020 ( 43 ) and one in 2022 ( 44 ) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As for the year, it was identified that the first publication was carried out in 1995 ( 17 ) , two new publications in 2001 ( 20 ) , one more in 2003 ( 21 ) and another in 2004 ( 22 ) , three publications in 2005 ( 38 ) one more was found, four in 2020 ( 43 ) and one in 2022 ( 44 ) .…”
Section: Resultsmentioning
confidence: 99%
“…With regard to language, 24 were published in English ( 38 ) . As for the location, 20 publications were ­produced in the United States of America (USA) ( 17 33 , 35 , 40 , 44 ) , three in Brazil ( 36 , 42 , 43 ) , three in India ( 34 , 39 41 ) and two in Japan ( 37 , 38 ) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations